2009
DOI: 10.1002/bjs.6307
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation for treatment of postoperative respiratory failure after oesophagectomy

Abstract: The use of NPPV for the treatment of postoperative ARF may decrease the incidence of endotracheal intubation and related complications, without increasing the risk of anastomotic leakage after oesophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
1
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 43 publications
1
55
1
8
Order By: Relevance
“…7 Although recent esophageal surgery is considered as a contraindication for NIV by some of the authors 7 , there are studies reporting the successful and safety use of NIV in the immediate early postoperative periods of laparoscopic Nissen fundoplication, Roux-en-Y gastric bypass, and even oesophagectomy. [8][9][10] So we decided to perform NIV to our patient early after procedure.…”
Section: Resultsmentioning
confidence: 99%
“…7 Although recent esophageal surgery is considered as a contraindication for NIV by some of the authors 7 , there are studies reporting the successful and safety use of NIV in the immediate early postoperative periods of laparoscopic Nissen fundoplication, Roux-en-Y gastric bypass, and even oesophagectomy. [8][9][10] So we decided to perform NIV to our patient early after procedure.…”
Section: Resultsmentioning
confidence: 99%
“…Exclusions were as a result of: Four articles were included for analysis. 8,[32][33][34] A PRISMA flow diagram 35 for the above process is provided in Figure 1.…”
Section: Search Strategymentioning
confidence: 99%
“…Settings that require special attention during NIV include recent gastrointestinal or upper airway surgery, inability to protect the airways, hemodynamic instability, decreased consciousness, vomiting, intestinal occlusion, undrained pneumothorax, and confusion and agitation states. Recent studies have shown that NIV can be successfully used in patients with hypercapnic coma (16) and after upper gastrointestinal surgery (17). The clinical setting is also important; if NIV is the ceiling of treatment and therefore the only treatment option, a relative contraindication can be accepted, whereas it may not be if intubation is considered appropriate.…”
Section: Non-invasive Ventilation In Copd Exacerbations and Other Caumentioning
confidence: 99%